Double-blind placebo-controlled trial of etanercept in the prevention of work disability in ankylosing spondylitis. Issue 11 (28th May 2010) - Barkham, Nick; Coates, Laura C; Keen, Helen; Hensor, Elizabeth; Fraser, Alexander; Redmond, Anthony; Cawkwell, Lorna; Emery, Paul
Abstract : Objectives: Etanercept has been shown to be rapidly effective in suppressing disease activity in ankylosing spondylitis (AS). The aim of this study was to determine whether etanercept improves work instability as measured by the Ankylosing Spondylitis Work Instability Scale (AS-WIS). Method: Forty patients with active AS who were in work but were work unstable were recruited. Patients were randomised to receive 25 mg etanercept or placebo twice weekly for 12 weeks. The primary outcome was change in AS-WIS at week 12. The AS-WIS is a patient-derived outcome measure which allows stratification of the risk of job loss. Secondary outcomes included clinical outcomes and gait parameters. Results: The mean improvement in AS-WIS score at week 12 was 2.75 in the etanercept group and 0.68 in the placebo group (p=0.125). The risk of job loss decreased for 11 (55%) of the etanercept group compared with 7 (35%) in the placebo group. Conversely, the risk of job loss increased in 3 (15%) of the placebo group compared with 1 (5%) in the etanercept group. There was no statistically significant difference between treatment groups in change in WIS categories (Mann–Whitney U test=0.153, p=0.160). Significant improvement with etanercept was seen at week 12 in clinical outcomes and gait parameters. Etanercept was well tolerated, with no dropouts due to adverse events. Conclusion: This small study confirms the efficacy of etanercept on clinical outcome measures in patients with AS and suggests an effect on work instability which needs to be replicated in a larger controlled study.